Kazakh zhyrau-poets and Sufi teachings - Ahmetbekova, А. К. (Journal of Oriental Studies, 2016)
islam was spread on Kazakh land to a greater extent due to interpretations of turk sufi poet Kozha akhmet yassaui who lived during Xiicentury. such conclusion arises from researching works of zhyrau-poets of Kazakh Khanate ages. thesaurus of zhyrau poetry and broad interpretation of islam principles indicate strong influence of sufism on Kazakhs’ confession. author points out on transformations of several sufi terminologies, which were determined as a result of historical circumstances and Kazakh mentality.